"Toleranz – du nervst mich so": Reinventing Lessing's Nathan der Weise for the Contemporary German Stage. (23rd November 2020) - Murnane, Barry
Abstract : Nathan der Weise is frequently used as a vehicle in contemporary German theatre to engage with the geopolitical ramifications of globalization such as inter‐faith conflict and violence. Despite this continuing popularity, the optimistic Enlightenment message of tolerance and toleration in Lessing's play is often criticized as inadequate in an age in which cosmopolitanism and transnational movement of people are seen as the source of rather than remedy to identity political tensions. This essay discusses two recent innovative responses to Lessing—Elfriede Jelinek's Abraumhalde (2009) and Emre Koyuncuoğlu's Nathan schweigt (2010)—and argues that contemporary female writers in particular have transformed Lessing's play to engage with questions of the patriarchal and economic power structures lurking behind his concept of tolerance, enabling a forceful critique of contemporary neoliberal identity politics.